Juridicial Review of Diversion Application Against Theft by Children - Fachri, Muh Ashar; Erlina; Amiruddin, Muh. (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
In juvenile criminal law, children are also involved in criminal acts. Children under 10 are usually not punished, while children aged 10-16 can be punished. However, in the enforcement of punishment for children, it is important to pay attention to their stage of development. The method in this study is normative way. The result showed that is is reflected in Law No. 11 of 2012 concerning the juvenile criminal justice system, where diversion is used as an alternative to settlement outside of Justice. However, in certain cases such a number: 10/Pid.Sus.Child/2020 / Fr. Sgm, diversion is not applied because it only applies to child offenders who first make mistakes. In this case, the offender has committed a repeated criminal offense, so the judge decides to give a criminal sentence.